2018
DOI: 10.1080/21691401.2018.1459633
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human hair keratin proteins for halting bleeding

Abstract: Keratins derived from human hair have been widely used for tissue engineering. However, some drawbacks relative to the traditional keratins extracts have been found: (a): difficultly controlling the amino acid composition; (b): batch to batch inconsistent quality; and (c): producing complex keratin and keratin-associated proteins (KAPs), which problems have made some studies concerning human hair keratins stagnant, especially in the mechanism studies related to hemostasis of keratins. Herein, a type-I human ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…Hemostatic nanoparticles with a particular size and curvature characteristics can stop internal bleeding more efficiently due to the strong bonding between the nanoparticles and the tissue surface . Previous studies have demonstrated that keratin nanoparticles can act as hemostatic materials in several animal models, such as bleeding from rabbits and pigs, , enhanced platelet binding and activation, and facilitated fibrinogen polymerization. , Therefore, the present study aimed to evaluate the hemostatic ability of the prepared keratin-associated proteins nanoparticles (KAPNPs) from human hair.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hemostatic nanoparticles with a particular size and curvature characteristics can stop internal bleeding more efficiently due to the strong bonding between the nanoparticles and the tissue surface . Previous studies have demonstrated that keratin nanoparticles can act as hemostatic materials in several animal models, such as bleeding from rabbits and pigs, , enhanced platelet binding and activation, and facilitated fibrinogen polymerization. , Therefore, the present study aimed to evaluate the hemostatic ability of the prepared keratin-associated proteins nanoparticles (KAPNPs) from human hair.…”
Section: Introductionmentioning
confidence: 99%
“…28 Previous studies have demonstrated that keratin nanoparticles can act as hemostatic materials in several animal models, such as bleeding from rabbits and pigs, 17,29 enhanced platelet binding and activation, and facilitated fibrinogen polymerization. 18,19 Therefore, the present study aimed to evaluate the hemostatic ability of the prepared keratinassociated proteins nanoparticles (KAPNPs) from human hair. In this study, as shown in Figure 1, we extracted KAPs from the keratin mixture of human hair.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations